Cambodian High School Students' Motivation in Learning English: One-Way ANOVA Analysis - Sereyrath Em; Nel Nun (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
English has become a world language. It has been used formally as the first, second, or third language in many countries worldwide. Therefore, for decades, English language learning and teaching have become the focus for educators, teachers, students, and all other concerned sponsors. There are different contributions to the success of English language learning and teaching. Motivation is one of the most important components that push students to succeed in learning English. The current study employed a quantitative design, analyzing the existing data of 265 Cambodian high school students to explore if there were significantly different motivation levels in learning English according to their grades and age ranges. The results prove that there were no significant differences across the students' grades and age ranges of motivation in learning English. Finally, a future study using different designs at other educational institutions or with a bigger sample size was suggested.